2010
DOI: 10.1080/01932690903110400
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis on the Influence of Indigenous Crude Oil Components on the Quality of Produced Water. Comparison Between Bench and Rig Scale Experiments

Abstract: A matrix of 30 crude oils have been analyzed to investigate if there is any correlation between the physiochemical properties of the crude oils and the quality of the produced water. As an approach to study produced water quality, oil. and brine water (3.5 wt%) have been mixed together, and transmission profiles from the separation process have been investigated by means of Turbiscan LAb. The Turbiscan LAb enables the study of stability of colloidal dispersions without any dilution or modification of the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Furthermore, the volume contribution of drops larger than 10 µm was negligible. The increased polydispersity in the emulsions, when the viscosity of the dispersed phase was higher, agreed with other reports 20,46 , even though the measurements were done subsequent to two hours of gravity separation.…”
Section: Produced Water Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the volume contribution of drops larger than 10 µm was negligible. The increased polydispersity in the emulsions, when the viscosity of the dispersed phase was higher, agreed with other reports 20,46 , even though the measurements were done subsequent to two hours of gravity separation.…”
Section: Produced Water Qualitysupporting
confidence: 91%
“…The interfacial activity of components in the crude oils will be affected by these parameters and can lead to increased emulsion stability and problems with separation [17][18] . It has been shown that the interfacial properties can influence the coalescence of oil droplets 19 and the stability of oilin-water emulsions [20][21] . Once in contact with an aqueous phase, water-soluble hydrocarbons in the crude oil will partition into the water phase [22][23][24] , adsorb at the gas-water interfaces and influence the oil removal efficiency by gas flotation [25][26] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A stirring tank was used by Angle et al, who followed the change in size distributions of toluene-diluted heavy oil in water emulsions upon variation of different parameters. ,, Some studies also attempted to correlate the crude oil composition with the water quality after separation. Silset et al conducted bench- and technical-scale experiments with a large matrix of oils to map the relation between the crude oil properties and the separation performance . Eftekhardadkhah and Øye investigated the effect of the crude oil and water composition on the concentration and interfacial activity of the dissolved components in PW .…”
Section: Introductionmentioning
confidence: 99%
“…Silset et al conducted bench-and technical-scale experiments with a large matrix of oils to map the relation between the crude oil properties and the separation performance. 28 Eftekhardadkhah and Øye investigated the effect of the crude oil and water composition on the concentration and interfacial activity of the dissolved components in PW. 29 Their study showed good correlation between the water quality and the presence of certain heteroatom-containing groups in crude oils.…”
Section: Introductionmentioning
confidence: 99%